PROFILE OF BALI COW FARMERS PARTICIPANTS OF UPSUS SIWAB IN GIANYAR DISTRICT - I K. A., Wiguna; Sarini, N P.; Suranjaya, I G. (Jurnal Peternakan Tropika; Vol 9 No 1 (2021): Vol. 9 No. 1 Tahun 2021; January - april, 2021)
The purpose of this study was to determine the different between Balinese cattle breeders who were participating UPSUS SIWAB and non UPSUS SIWAB in Gianyar Regency. It was also to find out the level of understanding of breeders on the management aspects on rearing cows with calves.  This research had conducted in Gianyar Regency for two months, where the number of respondents was 15 farmers on the UPSUS SIWAB group and 15 farmers on the non UPSUS SIWAB group, the method used was the survey method, using a questionnaire that has been compiled. Data obtained was analyzed using a two-sample free t test. There are 2 variables were observed such as the character of the bali cattle breeders and the management of the cows. The breeder's characters including: age, education, the length of experience, number of cattle own, the number of family members, and the reasons for raising cattle, and the management of raising cattle consists of: feed management, seed management, reproductive management and mating management.  The results showed that there were no significant differences in the breeder’s character, including: the age and work experience (P> 0.05), similar to the level of understanding and knowledge of the breeders to raise their cows. Mean while, there were significantly different in feed management, reproductive management and marriage management (P <0.05).  Howeever, there was no significant difference found on the aspect of seed selection (P> 0.05).  It can be concluded that the characters of UPSUS SIWAB and non-UPSUS SIWAB participating cattle breeders are categorized not different, and at the level of understanding of the management of cows, the UPSUS SIWAB participant breeders have a better understanding in carrying out the management of raising cow, especially on feed management, reproductive management, and marriage management. Key words: breeders, catlle, profile